Sustainable Management of Bacterial Fruit Blotch in Watermelon Using Biocontrol Agents at Tella, Taraba State - O., Phoebe A.; A., Tuwari B.; R., Umaru; Y., Madinatu (Darul Yasin Al Sys, 2025)
Bacterial fruit blotch (BFB), caused by Acidovorax citrulli, represents a significant challenge to watermelon cultivation in Nigeria, frequently resulting in substantial yield losses under conducive climatic conditions. This study aimed to evaluate the effectiveness of selected plant-based biocontrol agents in managing BFB and improving the growth and yield performance of three watermelon varieties: Sweet Sangaria, Kaolack, and a local landrace. A two-year field trial (2020–2021) was conducted in Tella, Taraba State, using a randomized complete block design with three replications. Treatments consisted of neem oil, garlic oil, jatropha oil, and their binary combinations, alongside streptomycin as a standard control and an untreated control plot. Results revealed that the plant-based treatments significantly reduced BFB incidence compared to the control, with some combinations performing comparably to streptomycin. Additionally, improvements were observed in plant growth parameters and fruit yield across all treated plots. The findings underscore the potential of botanical biocontrol agents as sustainable alternatives to synthetic antibiotics for managing BFB in watermelon cultivation, contributing to environmentally friendly disease management strategies suitable for smallholder farming systems.